Civic Education as an Integrated Knowledge System in the 21st Century: A Reform Approach - Suriaman, Suriaman; Komalasari, Kokom; Nurgiansah, T Heru; Prayogi, Ryan; Bribin, Maria Lufransiya (Universitas of Muhammadiyah Makassar, 2024)
The 21st century demands a cutting-edge Civic Education that transcends traditional boundaries and empowers individuals to become active, informed and responsible citizens. The problem is that the current state of civic education as an integrated knowledge system in the 21st century recognizes the importance of preparing individuals to be active participants in an open democratic society. By embracing an integrated knowledge system, through Civic Education, it can equip future generations of the nation with the systems and understanding necessary to build a more just, equal and sustainable world. The purpose of this study is to provide an overview of efforts in equipping students with the knowledge, skills and attitudes necessary for civic engagement, this approach seeks to create informed and responsible citizens who contribute positively to the students' community. This research uses a qualitative approach with a literature review method. The results of this analysis show that there needs to be an effort to reform the approach in learning Civic Education to prepare students as citizens who grow and develop in the 21st century starting from knowledge, skills, and attitudes as an integrated part in today's social complexity. Citizens must be prepared with a more reformist approach through 21st century skills-based education.